1987
DOI: 10.1083/jcb.105.5.2203
|View full text |Cite
|
Sign up to set email alerts
|

A microtubule-associated protein from Xenopus eggs that specifically promotes assembly at the plus-end.

Abstract: Abstract. We have isolated a protein factor from Xenopus eggs that promotes microtubule assembly in vitro. Assembly promotion was associated with a 215-kD protein after a 1,000-3,000-fold enrichment of activity. The 215-kD protein, termed Xenopus microtubule assembly protein (XMAP), binds to microtubules with a stoichiometry of 0.06 mol/mol tubulin dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
275
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(299 citation statements)
references
References 32 publications
21
275
2
Order By: Relevance
“…The founding member of this family, XMAP215, is required for rapid microtubule growth in Xenopus laevis egg extracts and accelerates elongation of the fastgrowing plus ends of microtubules by up to 8-fold in the presence of purified bovine brain tubulin (7). Tea1, the Aspergillus nidulans homolog of XMAP215, accelerates the growth of porcine brain microtubules to a similar extent as XMAP215 (8).…”
mentioning
confidence: 94%
“…The founding member of this family, XMAP215, is required for rapid microtubule growth in Xenopus laevis egg extracts and accelerates elongation of the fastgrowing plus ends of microtubules by up to 8-fold in the presence of purified bovine brain tubulin (7). Tea1, the Aspergillus nidulans homolog of XMAP215, accelerates the growth of porcine brain microtubules to a similar extent as XMAP215 (8).…”
mentioning
confidence: 94%
“…DdCP224 from D. discoideum was detected at the centrosome and more weakly along microtubules throughout the entire cell cycle; furthermore, it binds to microtubules in vitro (11). XMAP215 from Xenopus promotes the formation of long microtubules by increasing the rate of microtubule polymerization, particularly at the plus end (4,45). Expression of truncated segments of XMAP215 in vivo (46) showed that the entire protein participates in microtubule binding.…”
Section: Effect Of Togp On Tubulin Polymerization; Effect Of Tubulin mentioning
confidence: 99%
“…2 This last group is composed of structural MAPs (MAP2, tau) that were first identified in brain tissue and of a group of XMAP215-related proteins whose generic member was first characterized in Xenopus eggs (4). TOGp (HUGO gene CKAP5), which is highly expressed in tumors and brain (5), is the human homolog of XMAP215.…”
mentioning
confidence: 99%
“…It was identified as a factor increasing microtubule polymerization rates in Xenopus egg extracts (5). In vivo studies have shown that disruption of XMAP215 function leads to short interphase microtubules, reduced microtubule growth rate, and increased frequency of microtubule catastrophe and pause events (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%